Cardiovascular risk assessment of dyslipidemic middle-aged adults without overt cardiovascular disease over the period of 2009–2016 in Lithuania - Sandra Kutkiene; Zaneta Petrulioniene; Aleksandras Laucevicius; Pranas Serpytis; Vytautas Kasiulevicius; Justina Staigyte; Akvile Saulyte; Emilija Petrulionyte; Urte Gargalskaite; Egle Skiauteryte; Gabija Matuzeviciene; Milda Kovaite; et al. (Lipids in Health and Disease, 2018)
Abstract Background Cardiovascular mortality in Lithuania is extremely high and abnormal lipid levels are very common among Lithuanian adults. Dyslipidemia is one of the main independent risk factors for cardiovascular diseases (CVD) leading to high absolute CVD risk. The aim of this study was to assess CVD risk in dyslipidemic middle-aged subjects. Methods During the period of 2009–2016 a total of 92,373 people (58.4% women and 41.6% men) were evaluated. This study included men aged 40–54 and women aged 50–64 without overt CVD. Results Any type of dyslipidemia was present in 89.7% of all study population. 7.5% of dyslipidemic patients did not have any other conventional risk factors. Three and more risk factors were detected in 60.1% of dyslipidemic subjects. All analyzed risk factors, except smoking, were more common in dyslipidemic adults compared to subjects without dyslipidemia: arterial hypertension (55.8% vs. 43.3%, p < 0.001), diabetes (11.1% vs. 7.3%, p < 0.001), abdominal obesity (45.3% vs. 30.2%, p < 0.001), BMI ≥30 kg/m2 (35.8% vs. 23.7%, p < 0.001), metabolic syndrome (34.0% vs. 9.2%, p < 0.001), family history of coronary heart disease (26.3% vs. 23.1%, p < 0.001), unbalanced diet (62.5% vs. 52.9%, p < 0.001) and insufficient physical activity (52.0% vs. 44.2%, p < 0.001). The prevalence of all evaluated risk factors, except smoking, increased with age. Average SCORE index was 1.87 in all study population, while dyslipidemic subjects had higher SCORE compared to control group (1.95 vs 1.20, p < 0.001). Conclusions Almost two thirds of dyslipidemic middle-aged Lithuanian adults without overt cardiovascular disease had three or more other CVD risk factors, which synergistically increase absolute risk of CVD. The average 10-year risk of CVD death in patients with dyslipidemia was 1.95%. The importance of managing dyslipidemia as well as other risk factors in order to reduce burden of cardiovascular disease in Lithuania is evident.